Restoration of Neuromuscular Control During The Pitch After Operative Treatment Of Slap Tears. Issue 7 (29th July 2014) - Chalmers, Peter Nissen; Cip, Johannes; Trombley, Robert; Monson, Brett; Wimmer, Markus; Cole, Brian J.; Verma, Nikhil N.; Romeo, Anthony A.
Objectives: Superior labral anterior-posterior (SLAP) tears are a common cause of shoulder pain and dysfunction in overhead throwers. Treatment outcomes remain unpredictable with a large percentage of atheletes unable to return to sport. Persistent pain from the LHB (long head biceps) has been postulated as etiology of failure following repair. Previous authors have hypothesized that maximal stress is placed upon the biceps anchor during the cocking phase and that SLAP tears likely occur during this phase. We hypothesized that operative treatment of SLAP tears with repair or tenodesis would result in persistent alterations in neuromuscular control of the biceps during the overhand pitch post-operatively. Methods: We evaluated the activity of the biceps muscle in the overhand pitching motion and correlate this activity with throwing phase in healthy collegiate and semi-professional pitchers, collegiate pitchers status-post SLAP repair, and collegiate pitchers status-post biceps tenodesis. Patients were at least one year post-operative and had returned to pitching with a painless shoulder. Subjects pitched from a regulation-sized mound while surface electrodes collected electromyographic (sEMG) signals at 1500 Hz from the long- and short-heads of the biceps (LHBM and SHBM respectively), the deltoid, the infraspinatus, and the latissimus dorsi. Motion analysis data was captured at 120 Hz with a 14-camera three-dimensional markerless motion analysis system. At least five pitches were performed by each subject. sEMG data was then normalized to maximal manual muscle testing and then divided into previously described pitching phases (wind-up, stride, cocking, acceleration, deceleration, follow-through). Results: Eighteen pitchers participated: 7 normals, 6 status-post SLAP repair, and 5 status-post tenodesis. While no significant differences were observed in mean LHBM, SHBM, deltoid, infraspinatus, or latissimus activity between normals, pitchers status-post SLAP repair, and pitchers status-post tenodesis during each phase, loss of the normal activation contours was seen for both pitchers status-post SLAP repair and those status-post tenodesis, suggesting continued reflex inhibition. As confirmation, significantly less overactivity (>100% activity) was seen in post-operative deltoids than normal deltoids (p=0.025). Conclusion: Simultaneous EMG and motion analysis of pitchers status-post operative treatment of SLAP tears suggests that while tenodesis and repair may restore physiologic muscular activation amplitude, persistent changes in activation contours persist for both tenodesis and repair. Both treatments may have biomechanical and neuromuscular consequences, even in pitchers with a full painless return to play. Further study is needed to determine potential differences between patients with persistent pain following surgery, as well as differing treatment modalities (tenotomy, tenodesis, repair).